Socio-demographic, maternal, and child indicators of socioemotional problems in 2-year-old children: A cohort study. Issue 28 (July 2018) - Palmer, Frederick B.; Graff, Joyce C.; Jones, Tamekia L.; Murphy, Laura E.; Keisling, Bruce L.; Whitaker, Toni M.; Wang, Lei; Tylavsky, Frances A.
Abstract : Abstract: Throughout infancy and early childhood, stable and secure relationships with caregivers are needed to promote optimal socioemotional (SE) and cognitive development. The objective is to examine socio-demographic, maternal, and child indicators of SE problems in 2-year-olds living in an urban-suburban community in the southern United States. Mother–infant pairs enrolled in a prospective pregnancy cohort study. Shelby County (Memphis), Tennessee. One thousand five hundred three women were recruited during their second trimester and followed with their children through the child's age of 2 years. Child SE development was measured by the Brief Infant-Toddler Social Emotional Assessment at 2 years of age. Mothers reported their own behavioral and mental health, temperament, parenting stress, and potential for child abuse during gestation and/or when their child was 1 year of age. Examiners measured maternal IQ during data collection at the child's age of 1 year. Child communication, cognitive development, and risk for autism spectrum disorder were assessed at 1 and 2 years of age. Multivariable regression models were developed to predict mother-reported SE problems. In bivariate analyses, multiple maternal behavioral and mental health indicators and child cognitive skills were associated with reported child SE problems at 2 years of age. Regression analyses, controlling for socio-demographic, maternal, and child variables, showed the following factors were independently associated with mother-reported child SE problems: maternal education of high school or less, lower maternal IQ, higher maternal cyclothymic temperament score, greater parenting stress, greater maternal psychological distress, lower child expressive communication score, and child risk for autism spectrum disorder. Socio-demographic variables accounted for the variance often attributed to race. Since mothers in the study were medically low-risk, generalizing these findings to medically high-risk mothers is unwarranted. In addition, these SE outcomes in 2-year-old children do not reflect the trajectory of SE development throughout early childhood. Attention to independent indicators of future SE problems in children may help identify individual children and families needing intervention and target public prevention/treatment programs in communities.